The Effect of Human Resource Quality on Employee Performance at the Ulubongka District Office, Tojo Una-Una Regency - Hartati, Dita; Andi Indriani Ibrahim; Lindanur Sipatu; Wisra Matalatta; Rosida P. Adam (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to examine the effect of human resource quality on employee performance at the Ulubongka District Office, Tojo Una-Una Regency. A quantitative approach with a causal research design was employed. The study involved all 31 employees using a total sampling technique. Data was analyzed using simple linear regression. The results indicate that human resource quality has a positive and significant effect on employee performance. Higher levels of knowledge, work ability, work attitude, and professional behavior contribute to improved employee performance. However, unstable internet connectivity and frequent power outages remain major challenges affecting employees' work performance. Keywords: Human Resource Quality, Employee Performance